2012
DOI: 10.1155/2012/863947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abiotic Factors on the Geographic Distribution of Body Size Variation and Chromosomal Polymorphisms in Two Neotropical Grasshopper Species (Dichroplus: Melanoplinae: Acrididae)

Abstract: We review the effects of abiotic factors on body size in two grasshopper species with large geographical distributions: Dichroplus pratensis and D. vittatus, inhabiting Argentina in diverse natural habitats. Geographical spans for both species provide an opportunity to study the effects of changes in abiotic factors on body size. The analyses of body size distribution in both species revealed a converse Bergmannian pattern: body size is positively correlated with latitude, altitude, and seasonality that influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…According to this theory, animal body size varies with altitude and latitude (Bidau et al, 2012). Hepburn et al (2001), by means of morphometric analysis, recorded that in the honeybee Apis cerana the body size increases with altitude, results congruent with this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to this theory, animal body size varies with altitude and latitude (Bidau et al, 2012). Hepburn et al (2001), by means of morphometric analysis, recorded that in the honeybee Apis cerana the body size increases with altitude, results congruent with this study.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were found in this study, where body size was apparently more affected by the different habitats than the shape of these individuals. Bidau et al (2012) found that body size in species of grasshoppers is positively correlated with latitude, altitude, and seasonality, and that these factors influence development and growth.…”
Section: Discussionmentioning
confidence: 98%
“…In South American acridid grasshoppers Rb translocation polymorphisms are frequent in central, stable and highly productive environments, and decline to monomorphism towards the southern extreme of the range, which is characterized by harsh, highly seasonal and variable habitats (Bidau & Martí ; Bidau et al . ). Several hypotheses have been suggested to explain this pattern, including the central‐marginal hypothesis that predicts lower diversity at the margins of species' distributions (Kirkpatrick & Barton ).…”
Section: Maintenance Of Adaptationmentioning
confidence: 97%
“…This has been observed in at least two study systems, each involving a different chromosomal rearrangement: Rb translocation polymorphisms in grasshoppers (Dichroplus pratensis) and chromosomal fissions in blind mole rats (Spalax spp.). In South American acridid grasshoppers Rb translocation polymorphisms are frequent in central, stable and highly productive environments, and decline to monomorphism towards the southern extreme of the range, which is characterized by harsh, highly seasonal and variable habitats (Bidau & Mart ı 2002;Bidau et al 2012). Several hypotheses have been suggested to explain this pattern, including the central-marginal hypothesis that predicts lower diversity at the margins of species' distributions (Kirkpatrick & Barton 1997).…”
Section: Genomic Mechanisms Maintaining Adaptation Despite Gene Flowmentioning
confidence: 99%
“…In insects with generation times on par with the growing season, such as I. rizeensis , an increase in seasonality usually leads to a reduction in body size, since development time is heavily constrained. This pattern is well supported for many univoltine Orthoptera species (Çıplak et al ., ; Lehmann & Lehmann, ; Whitman, ; Bidau et al ., ). However, the general model linking development with available time for growth assumes constant growth rates within species.…”
Section: Discussionmentioning
confidence: 97%